Ecohydrology for compensation of Global Change - Zalewski,M. (2010)
Water in the XXI century has become the primary factor for sustainable development, eradication of poverty and reversal of ecosystem degradation. Increasing water demand for agriculture and urbanisation, combined with pollution, eutrophication and amplification of the stochastic character of climatic processes, increases water limitations for ecosystems and societies. The transdisciplinary science of Ecohydrology, which has been developed in the framework of the International Hydrological Programme of UNESCO, provides a systemic approach, to regulate hydrology-ecosystem-society interplay towards: 1) slowing down the transfer of water from the atmosphere to the sea, still considered as a priority to reduce the severity of floods and droughts impact; 2) reducing input and regulating the allocation of excess nutrients and pollutants to aquatic ecosystems, toward reversing ecosystems degradation and improvement of human well being; and 3) harmonisation of ecosystem potential with societal needs within the framework of IWRM.